Leg attack proficiency and physical fitness of national tournament winners among Japanese male elementary (U-12) and junior high school wrestlers (U-15) - Kimura, M.; Aizawa, K.; Watanabe, E.; Satoh, M.; Mishima, T. (International Journal of Wrestling Science, 2024)
This research aims to clarify the relationship between the tackle technique and physical fitness/motor skills of male elementary school wrestlers(U-12) and junior high school wrestlers(U-15). It also aims to compare the developmental trends of physical fitness and motor skills from the perspective of competitive levels and create foundational data contributing to the development of wrestling skills. The participants included 69 male wrestlers from 5th grade elementary to 3rd grade middle school. The measured variables consisted of height, weight, body fat percentage, standing long jump, lateral jump (side steps), and repetition training of the tackle technique used in actual wrestling practice. As a result, it was suggested that explosive power and agility may be involved in the tackle technique of elementary and middle school wrestlers who win medals at national tournaments in Japan. Furthermore, it was revealed that medal-winning athletes excel in agility, and the proficiency in tackle technique differs at the boundary of the middle school level.